Designing an Automated Composter for Food Waste Management with the Implementation of Internet of Things - Fakharulrazi, Alyani Nadhiya; Yakub, Fitri (Journal of Sustainable Natural Resources, 2020)
The objective of his paper is build a fully automated composting machine that can help to reduce food waste using a more efficient and environmental friendly method. This machine has its special features of heating, cooling and grinding which is simple and easy to use for every consumer at just one touch of a button. In addition, it uses a special filter to eliminate unpleasant odor to ensure consumer’s space of mind. The process of composting uses node microcontroller (MCU) to run its operation and using Internet of Things (IoT) with a developed mobile application to measure the amount of food waste, current process and its moisture content before turning the waste into high nutrient flakes at around 10% of its original volume. It will also notify the consumer when the whole process is done and the final product is ready to use. The produced flakes are good for nurturing soils, use as fertilizer, and renewable source of energy or animal feed. The benefit is to help reduce handling cost at landfill. Excessive logistical energy is required to send food waste to landfill if applied conventional equipment. This product has a high potential to penetrate the end users who usually cooks at home and also the industrial food manufacturer, whether from medium to large which produces a lot of raw waste. Essentially, this machine can results less food waste been thrown through implementation of IoT and change it to usable fertilizer also helps in pest control.